Penapisan Hipertensi Pada Guru SMA Santo Yoseph, Cakung, Jakarta Timur - Denny Denny; Alexander Halim Santoso; Ryan Dafano Putra Mahendri; Steven Hizkia Lucius; Andrew Philo (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
High blood pressure or hypertension is a significant global public health problem, especially in the productive age group (18-64 years). Hypertension often does not show symptoms in the early stages, but if left untreated, it can lead to serious complications such as cardiovascular disease, stroke, and kidney failure. This Community Service activity was carried out on teachers at Santo Yoseph High School, Cakung, East Jakarta. The purpose of this activity is to screen for hypertension through blood pressure checks. This activity was designed using the Plan-Do-Check-Action (PDCA) method as a sustainable method for processes or activities. The results showed that 27 teachers (38.04%) had high blood pressure. This screening program is important because it can increase public awareness of hypertension, which can be prevented by monitoring blood pressure early and regularly, so that it can improve overall health outcomes and quality of life.